2018
DOI: 10.1021/acs.jmedchem.8b01757
|View full text |Cite
|
Sign up to set email alerts
|

Potent Metabolic Sialylation Inhibitors Based on C-5-Modified Fluorinated Sialic Acids

Abstract: Sialic acid sugars on mammalian cells regulate numerous biological processes, while aberrant expression of sialic acid is associated with diseases such as cancer and pathogenic infection. Inhibition of the sialic acid biosynthesis may therefore hold considerable therapeutic potential. To effectively decrease the sialic acid expression, we synthesized C-5-modified 3-fluoro sialic acid sialyltransferase inhibitors. We found that C-5 carbamates significantly enhanced and prolonged the inhibitory activity in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 32 publications
1
75
1
Order By: Relevance
“…To the best of our knowledge, immobilized NAL has never been used in a continuous flow setup for the preparation of synthetic Neu5Ac derivatives. Based on the broad experience with chemoenzymatic reactions in our group, both in batch and in flow systems, and on our expertise in the chemistry and biology of sialic acids, we herewith report a straightforward continuous flow system containing immobilized NAL providing a new and efficient chemoenzymatic entry into biologically relevant N ‐functionalized Neu5Ac derivatives.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, immobilized NAL has never been used in a continuous flow setup for the preparation of synthetic Neu5Ac derivatives. Based on the broad experience with chemoenzymatic reactions in our group, both in batch and in flow systems, and on our expertise in the chemistry and biology of sialic acids, we herewith report a straightforward continuous flow system containing immobilized NAL providing a new and efficient chemoenzymatic entry into biologically relevant N ‐functionalized Neu5Ac derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to monitoring conversions, the sialic acid products 11 – 17 were also obtained in fairly reasonable isolated yields confirming the synthetic feasibility of this system (Scheme ). This includes the propargyloxycarbonyl (Poc)‐functionalized Neu5Ac derivative 16 which has been extensively used in our group and was shown to be an effective substrate in bioorthogonal glycobiology research …”
Section: Methodsmentioning
confidence: 99%
“…As a result, cells lost their selectin binding affinity, and leukocyte rolling was damaged. It has been recently shown that 5-carbamate derivatives of peracetylated-[3F ax ]-Neu5Ac exhibited a prolonged and increased inhibition of STs in several cell lines [ 406 ].…”
Section: Carbohydrate Processing Inhibitorsmentioning
confidence: 99%
“…Recently, Siglec-9 and Siglec-15 have been reported as crucial inhibitors of anti-tumor immunity, which can be blocked by mAbs in the novel anticancer management [103,104]. Recent advances in the field of immunotherapy suggest that targeting Siglec receptors with specific antibodies or fluorinated sialic acid analogs, called "false sialic acids," help to control autoimmunity, pathogen invasion, and malignancies [105,106].…”
Section: Cancer Progressionmentioning
confidence: 99%